Bolstering Poverty Reduction in Rwanda : A Poverty Assessment - World Bank (World Bank, Washington, DC, 2020)
Rwanda is renowned among African countries for the rapid advances achieved in its population’s standard of living. Public service delivery has grown dramatically, and educational attainment, vaccination rates, educational attainment, and demographic factors have all improved. Access to financial services, health insurance, and infrastructure have expanded. Between 2000 and 2010, the percentage of people living in poverty fell from 59 to approximately 46 percent and then to 38 percent by 2016 (NISR: national poverty line). Yet progress has not always been even, and challenges endure. With the COVID-19 pandemic, Rwanda will face fiscal strains and economic setbacks, in addition to public health difficulties. It will be paramount to identify and implement cost-effective policies that foster broad-based growth and sustained poverty reduction, while building resilience to a range of shocks. This poverty assessment provides empirical evidence regarding the constraints to accelerated poverty reduction over the period October-September 2010-11-2016-17 to help guide the country’s policies going forward.